Bouncing Back : Forests, Trees, and Resilient Households - Dewees, Peter (PROFOR, Washington, DC, 2013)
This paper examines some of the concepts surrounding the idea that forests and trees can contribute to making households more resilient to food insecurity. The paper begins with a discussion of the widely accepted definitions of food security, and the implications for our understanding of the role of forests and trees in contributing to food security. Authors discuss the origins of the idea of resilience, adaptability, and transformation as responses to food insecurity, and the conditions that increase the capacity of households to become resilient. The second part of the paper looks at some of the empirical evidence about the role of forests and trees as household safety nets, and examines some of the issues around the reliance on non-timber forest products (particularly wood-fuel) to produce income. The paper closes with a discussion of evolving perspectives about landscape approaches, how these can contribute to building household resilience to food insecurity, and some of the policies that can support this goal.